History and trends of the colloquiums - Peldschus, Friedel; Kapliński, Oleg; Zavadskas, Edmundas Kazimieras; Kaklauskas, Arturas (Technological and Economic Development of Economy, 2006)
In the article the 20 years experience of the colloquiums on the application of the multiple criteria methods in construction which were organised by Lithuanian, Polish and German colleaques is analyzed. A total of 10 colloquiums were organised whose participants have published some tens of books and more than 200 of scientific articles. The most important scientific trends are examined in the paper and results achieved are analyzed.Article in German.Historie und Trends des KolloquiumsZusammenfassung. Im Bericht wird die 20‐jährige Erfahrung der Kolloquien über die Anwendung der Mehrkriteriellen Methoden im Bau, die von litauischen, polnischen und deutschen Hochschulen organisiert wurden, analysiert. Es wurden insgesamt 10 Kolloquien organisiert, deren Teilnehmer einige Zehner von Büchern und über 200 von wissenschaftlichen Berichten veröffentlicht haben. Es wurden die wichtigsten im Bericht untersuchte wissenschaftliche Trends und erreichte Resultate analysiert.Schlüsselwörter: Bau, Mehrkriterielle Methoden, internationale Zusammenarbeit, Resultate.Tarptautinių kolokviumų istorija ir kryptysSantrauka. Apžvelgiama 20 metų Lietuvos, Lenkijos ir Vokietijos aukštųjų mokyklų organizuojamų kolokviumų daugiatikslių metodų taikymo statyboje klausimais patirtis. Iš viso įvyko 10 kolokviumų, kuriu dalyviai paskelbė keliasdešimt knygų ir apie 200 mokslo straipsnių. Apžvelgtos pagrindinės nagrinėtosios mokslo kryptys ir pasiekti rezultatai.Reikšminiai žodžiai: statyba, daugiatiksliai metodai, tarptautinis bendradarbiavimas, rezultatai.First Published Online: 21 Oct 2010